Joseph Krumgold's …And Now Miguel and Onion John: The Temper of the Times and the Encounter with the Other. (7th June 2021) - Nodelman, Perry
Abstract: A newcomer to writing for children, Joseph Krumgold revealed an intuitive mastery of what led to success in children's publishing in the 1950s, winning the American Library Association's Newbery Medal for distinguished contributions to children's literature for both of his first two novels: …And Now Miguel (1953) and Onion John (1959). An exploration of the novels reveals what made for distinction at that time, what assumptions about excellence for child readers the novels imply, and in doing so, what ideas they foster about who children are and how they do and should read. This essay reads the novels both in the wider context of bestselling 1950s books that offer theories about changing American values, and in terms of the specific values espoused by children's writers, publishers and librarians. A consideration of these matters reveals a metafictional relationship between the two novels that enriches the insights they offer into assumptions about children's reading.